Whole-Genome Resequencing of Spontaneous Oxidative Stress-Resistant Mutants Reveals an Antioxidant System of Bradyrhizobium japonicum Involved in Soybean Colonization - Liebrenz, Karen Ivana; Gomez, Maria Cristina; Brambilla, Silvina Maricel; Frare, Romina Alejandra; Stritzler, Margarita; Maguire, Vanina; Ruiz, Oscar; Soldini, Diego Omar; Pascuan, Cecilia Gabriela; Soto, Gabriela Cynthia; Ayub, Nicolás Daniel (Springer, 2021)
Soybean is the most inoculant-consuming crop in the world, carrying strains belonging to the extremely related species Bradyrhizobium japonicum and Bradyrhizobium diazoefficiens. Currently, it is well known that B. japonicum has higher efficiency of soybean colonization than B. diazoefficiens, but the molecular mechanism underlying this differential symbiotic performance remains unclear. In the present study, genome resequencing of four spontaneous oxidative stress–resistant mutants derived from the commercial strain B. japonicum E109 combined with molecular and physiological studies allowed identifying an antioxidant cluster (BjAC) containing a transcriptional regulator (glxA) that controls the expression of a catalase (catA) and a phosphohydrolase (yfbR) related to the hydrolysis of hydrogen peroxide and oxidized nucleotides, respectively. Integrated synteny and phylogenetic analyses supported the fact that BjAC emergence in the B. japonicum lineage occurred after its divergence from the B. diazoefficiens lineage. The transformation of the model bacterium B. diazoefficiens USDA110 with BjAC from E109 significantly increased its ability to colonize soybean roots, experimentally recapitulating the beneficial effects of the occurrence of BjAC in B. japonicum. In addition, the glxA mutation significantly increased the nodulation competitiveness and plant growth–promoting efficiency of E109. Finally, the potential applications of these types of non-genetically modified mutant microbes in soybean production worldwide are discussed.